2005
DOI: 10.1021/bi051122c
|View full text |Cite
|
Sign up to set email alerts
|

SR-Rich Motif Plays a Pivotal Role in Recombinant SARS Coronavirus Nucleocapsid Protein Multimerization

Abstract: The nucleocapsid (N) protein of SARS coronavirus (SARS-CoV) is reported to function in encapsidating the viral genomic RNA into helical nucleocapsid, and its self-association is believed to be vital in coating the viral genomic RNA. Characterization of SARS-CoV N multimerization may thereby help us better understand the coronavirus assembly. In the current work, using the yeast two-hybrid technique, an unexpected interaction between residues 1-210 and 211-290 (central region) of the SARS-CoV N protein was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 27 publications
1
67
0
Order By: Relevance
“…The oligomerization of the full-length SARS-CoV N protein has been studied widely (20)(21)(22)(23)(24), and its carboxyl terminal was proved to be necessary for its self-association (20,23). It was discovered previously that the C-terminal domain is able to form multimers (25), but it was not clear how high the formed oligomers could be, and the primary sequence for the oligomerization remained unclear. In this work, to investigate the oligomeric properties of the C-terminal domain (residues 283-422, N 283-422 ), the gel filtration (Figure 1), chemical cross-linking, and native gel electrophoresis technology based assays ( Figure 2) were applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oligomerization of the full-length SARS-CoV N protein has been studied widely (20)(21)(22)(23)(24), and its carboxyl terminal was proved to be necessary for its self-association (20,23). It was discovered previously that the C-terminal domain is able to form multimers (25), but it was not clear how high the formed oligomers could be, and the primary sequence for the oligomerization remained unclear. In this work, to investigate the oligomeric properties of the C-terminal domain (residues 283-422, N 283-422 ), the gel filtration (Figure 1), chemical cross-linking, and native gel electrophoresis technology based assays ( Figure 2) were applied.…”
Section: Methodsmentioning
confidence: 99%
“…The self-association domain in SARS-CoV N was first mapped out as the C-terminal 209 amino acids using the yeast twohybrid (23). Later this domain was shortened to the Cterminal 138 (residues 285-422) (20) and 140 (residues 283-422) amino acids (25) by two independent groups. Yu et al reported that residues 285-422 of SARS-CoV N formed only dimers (20), while our previous work revealed that residues 283-422 formed not only dimers but also multimers (25).…”
mentioning
confidence: 99%
“…The N-terminal domain (ϳ130 residues) folds similarly to the U1A RNA-binding protein and is suggested to bind RNA (11,12). The C-terminal domain contributes to its di-or multimerization assembly (13,14), and the central region contains a serine/ arginine (SR)-rich motif with unknown function but which is possibly also involved in the regulation of its multimerization (15). Notably, N proteins are highly phosphorylated in infected cells (16,17).…”
mentioning
confidence: 99%
“…Nevertheless, Surjit et al [56] demonstrated that the C-terminal 209 amino-acid region constitutes the interaction domain responsible for self-association of SARS-CoV N protein to form dimers. While a recent work [57] has provided an incongruent result, which demonstrates that the C-terminal domain of SARSCoV N protein (residues 283-422) has multimeric ability, although the full-length protein tends to form dimers. Further study revealed that the multimeric ability of the Cterminal domain could by weakened by the SR-rich motif interaction with the central region (residues 211-290), and suggested that the SR-rich motif might play an important role in the transformation of SARS-CoV N protein between the dimer and multimer for self-association or dissociation.…”
Section: Nucleocapsid (N) Proteinmentioning
confidence: 98%